Identifikasi Potensi Air Tanah untuk Kebutuhan Penyediaan Air Bersih dengan Metode Geolistrik: Studi Kasus di Kawasan Geostech, Puspiptek Serpong - Naryanto, Heru Sri; Khaerani, Puspa; Trisnafiah, Syakira; Shomim, Achmad Fakhrus; Wisyanto, Wisyanto; Tejakusuma, Iwan Gunawan (Jurnal Teknologi Lingkungan, 2020)
ABSTRACTGeostech Building, as an office and laboratory facility, requires a source of clean water from groundwater related to the limited supply of clean water from the PDAM. Due to the needs of freshwater from groundwater origin, data and information are needed regarding the potential groundwater in the area, including aquifer configuration, depth, and groundwater potential. The presence of groundwater is not distributed through every area, and it's related to the geological and geohydrological conditions. One of the geophysical methods that can describe subsurface is 2D geoelectric methods. This method can distinguish and analyze rock types, geological structures, groundwater aquifers, and other important information based on the characteristics of the electricity of rocks by looking at the value of the type of resistance. In this measurement, the Wenner Alpha configuration has been used, where the arrangement of A-B current electrodes and M-N potential electrodes have constant spacing. From the measurement results, it can be interpreted that there is a low resistivity layer containing porous groundwater as an aquifer. Based on regional geological data, it has been estimated that this layer is in the form of sandy tuff (0-1.5 ohm-m). The exploitation of groundwater with drilling is expected to reach the aquifer's upper layer at depth, starting from 11.5-13 meters. The groundwater aquifer thickness cannot be ascertained because of the penetration of the lower depth of 2D geoelectric measurements truncated by the constraint of a maximum stretch of cable. The upper layer of the aquifer contains a turned layer of fine tufa and medium tuff, which is impermeable, coarse tuff, and mixed soil with varying thickness at the upper layer.Keywords:Ã‚Â 2D geoelectric,Ã‚Â aquifer, potential groundwater, GeostechÃ‚Â Ã‚Â ABSTRAKGedung Geostech sebagai sarana perkantoranÃ‚Â dan laboratorium memerlukanÃ‚Â sumberÃ‚Â airÃ‚Â bersih dari air tanah terkait dengan terbatasnyaÃ‚Â suplaiÃ‚Â air bersih dari PDAM.Ã‚Â Kebutuhan air bersih berasal dari air tanah, maka diperlukan data dan informasi mengenai kondisi potensiÃ‚Â air tanahÃ‚Â di kawasanÃ‚Â tersebutÃ‚Â termasuk konfigurasiÃ‚Â akuifer, kedalaman, dan potensiÃ‚Â air tanahnya. KeberadaanÃ‚Â air tanahÃ‚Â tidaklahÃ‚Â merataÃ‚Â untukÃ‚Â setiapÃ‚Â tempatÃ‚Â danÃ‚Â sangatÃ‚Â terkaitÃ‚Â denganÃ‚Â kondisiÃ‚Â geologiÃ‚Â danÃ‚Â geohidrologinya. Salah satu metode geofisika yang dapat memberikan gambaran kondisi bawah permukaan adalah dengan metode geolistrik 2D. Metode ini dapat membedakan dan menganalisis jenis batuan, struktur geologi, akuifer air tanah, dan informasi penting lainnya berdasarkan sifat kelistrikan batuan dengan melihat nilai tahanan jenisnya. Dalam pengukuranÃ‚Â iniÃ‚Â digunakanÃ‚Â konfigurasiÃ‚Â Wenner Alpha,Ã‚Â dimanaÃ‚Â susunanÃ‚Â elektrodaÃ‚Â arusÃ‚Â AÃ‚Â danÃ‚Â B dan elektrodaÃ‚Â potensial M danÃ‚Â N mempunyaiÃ‚Â spasi yangÃ‚Â konstan.Ã‚Â Dari hasil pengukuran dapat diinterpretasikan adanyaÃ‚Â lapisan dengan resistivitas rendah yang mengandung air tanah dan bersifat porous sebagai akuifer. Berdasarkan data geologi regional diperkirakan lapisan ini berupa tuf pasiran (0-1,5 ohm-m).Ã‚Â Pengambilan air tanah dengan pemboran diperkirakan akan mengenai batas atas lapisan akuifer pada kedalaman 11,5-13 meter. Ketebalan akuifer air tanah tidak bisa dihitung karena penetrasi kedalaman pengukuran geolistrik 2D terbatasi oleh bentangan elektroda di permukaan. Lapisan di atas akuifer merupakan lapisan selang-seling tuf halus dan tuf sedang yang kedap air,Ã‚Â tuf kasar,Ã‚Â dan pada bagian paling atas merupakan tanah urugan dengan ketebalan bervariasi.Kata kunci: Geolistrik 2D, akuifer, potensi air tanah, GeostechÃ‚Â Ã‚Â